Spatial Structure Regulation: A Rod‐Shaped Viologen Enables Long Lifetime in Aqueous Redox Flow Batteries - Li, Hongbin; Fan, Hao; Hu, Bo; Hu, Linlin; Chang, Gang; Song, Jiangxuan (Angewandte Chemie International Edition, 2021)
A stable rod‐like sulfonated viologen (R‐Vi) derivative is developed through a spatial‐structure‐adjustment strategy for neutral aqueous organic redox flow batteries (AORFBs). The obtained R‐Vi features four individual methyl groups on the 2,2′,6,6′‐positions of the 4,4′‐bipyridine core ring. The tethered methyls confine the movement of the alkyl chain as well as the sulfonic anion, thus driving the spatial structure from sigmoid to rod shape. The R‐Vi with weak charge attraction and large molecular dimension displays an ultralow membrane permeability that is only 14.7 % of that of typical sigmoid viologen. Moreover, the electron‐donating effect of methyls endows R‐Vi with the lowest redox potential of −0.55 V vs. SHE among one‐electron‐storage viologen‐based AORFBs. The AORFB with the R‐Vi anolyte and a K4Fe(CN)6 catholyte exhibits an energy efficiency up to 87 % and extremely low capacity‐fade rate of 0.007 % per cycle in 3200 continuous cycles. We report a rod‐like sulfonated viologen (R‐Vi) anolyte for aqueous redox flow batteries (AORFBs). R‐Vi possesses a low membrane‐penetration rate of ≈10−10 cm2 s−1 and the lowest redox potential of −0.55 V vs. SHE among one‐electron‐storage viologens in AORFBs simultaneously. The R‐Vi‐based AORFB exhibits an extremely low capacity‐fade rate of 0.007 % per cycle in 3200 continuous charging–discharging processes.